(untitled) (Bangladesh Journal of Medical Science, 2011)
Background: Bangladesh has a neonatal death rate that is substantially high and demands urgent attention. Objective: This retrospective study was performed to determine the incidence of bacterial neonatal sepsis condition in the Chittagong area of Bangladesh with focus on various demographic characteristics of neonates, causative organisms and their antibiotic susceptibility. Methodology: Blood culture was performed on all neonates with risk factors or signs of suggestive sepsis. Blood samples were cultured using tryptone soya broth (TSB- blood broth) according to standard method. Results: From the 1400 neonates 104 had positive blood culture for neonatal sepsis infection. Among the infected children 40 (38.46%) were born in the hospital and 64 (61.54%) were born at home. The EONS (Early Onset Neonatal Sepsis) accounted for 68 (65.38%) and LONS (Late Onset Neonatal Sepsis) accounted for 36 (34.62%). Among the isolated organism Klebsiella pneumoniae accounted for 79 (75.96%), Serratia marcescens 19 (18.27%), Pseudomonas aeruginosa 04 (3.85%) and Staphylococcus aureus accounted for 02 (1.92%). Among the isolated species 102 were attributed to G (-ve) bacteria and 02 were attributed to G (+ve) bacteria. Most of the G (-ve) bacteria showed resistance to commonly used antibiotics such as ampicillin, ceftriaxon and gentamicin. In this study all isolates showed sensitivity to the imipenem. Conclusion: Collection of up-to-date data is mandatory for appropriate use of antibiotics. Key words: Neonatal sepsis, Interleukin-6, antibiotics, susceptibility. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8363 BJMS 2011; 10(3): 187-194